Clinical Outcomes and Diagnostic Consistency of Serum and CSF Tumor Markers in Pediatric Intracranial Germ Cell Tumors in Thailand: A Multicenter Study - Lalita Sathitsamitphong MD; Chalinee Monsereenusorn MD; Piti Techavichit MD; Kanjana Shotelersuk MD; Piradee Suwanpakdee MD; Piya Rujkijyanont MD; Pimlak Charoenkwan MD (SAGE Publishing, 2022)
The diagnostic and treatment outcomes of intracranial germ cell tumors (ICGCTs) among low and middle income countries are limited. A total of 63 ICGCTs patients with a median age of 11.6 years were studied. A 30 (47.6%) and 33 (52.4%) patients were classified as pure germinomas and nongerminomatous germ cell tumors (NGGCTs), respectively. The concordances between serum and cerebrospinal fluid (CSF) alpha-fetoprotein (84.3%) and beta-human chorionic gonadotropin (68.4%) were addressed. The 5-year overall survival (OS) and event-free survival (EFS) rates of pure germinomas versus NGGCTs were 83.9 versus 69.1% and 74.6 versus 57.7%, respectively. Patients undergoing radiation had higher 5-year OS and EFS than those without radiation treatment with P  < .001. Chemotherapy combined with radiation is a cornerstone treatment to achieve outcomes. Adverse prognostic factors included age <8 years, surgery, and nonradiation treatment. Either serum or CSF tumor markers were adequately required as a diagnostic test among patients with ICGCTs.